Aspergillus flavus resident in Kenya: High genetic diversity in an ancient population primarily shaped by clonal reproduction and mutation-driven evolution. (October 2018) - Islam, Md-Sajedul; Callicott, Kenneth A.; Mutegi, Charity; Bandyopadhyay, Ranajit; Cotty, Peter J.
Abstract: Aspergillus flavus has long been considered to be an asexual species. Although a sexual stage was recently reported for this species from in vitro studies, the amount of recombination ongoing in natural populations and the genetic distance across which meiosis occurs is largely unknown. In the current study, genetic diversity, reproduction and evolution of natural A. flavus populations endemic to Kenya were examined. A total of 2744 isolates recovered from 629 maize-field soils across southern Kenya in two consecutive seasons were characterized at 17 SSR loci, revealing high genetic diversity (9-72 alleles/locus and 2140 haplotypes). Clonal reproduction and persistence of clonal lineages predominated, with many identical haplotypes occurring in multiple soil samples and both seasons. Genetic analyses predicted three distinct lineages with linkage disequilibrium and evolutionary relationships among haplotypes within each lineage suggesting mutation-driven evolution followed by clonal reproduction. Low genetic differentiation among adjacent communities reflected frequent short distance dispersal.